ANALISIS PERLINDUNGAN HUKUM TERHADAP PEMUTUSAN HUBUNGAN KERJA SEPIHAK OLEH PENGUSAHA TERHADAP PEKERJA WANITA SAKIT: CONTOH KASUS PUTUSAN NOMOR 74/PDT.SUS-PHI/2019/PN.BDG JO. PUTUSAN NOMOR 1016 K/PDT.SUS-PHI/2019) - Tamara Ratnasari; Sugandi Ishak (Fakultas Hukum Universitas Tarumanagara, 2020)
Labor has a critical role in Indonesian economy, so in order to maintain the legal certainty and welfare of the parties involved in the work relationship, legal protection is needed for all parties. Not only is the certainty of legal protection for healthy laborers important, but also for ailing laborers who are prone to termination of employment due to poorer work performance compared to healthier peers. However, even though legal protection has been facilitated by law, incidents of illegal termination with severance pay that are not in accordance with Indonesian Labor Law often occurs. Thus, problems arise regarding the differences between the legal protection envisioned in the law and the reality that ensues regarding the laborers legal protection. This research type is a normative research with prescriptive objects. The conclusion from the results of the research is that the legal protection provided within the Indonesian labor law is already excellent, although it still requires the willingness of all the parties involved in the labor industry to learn and abide by the law and socialization of the applicable law so the ailing or healthy laborers are able to demand their rights comprehensively.